The Crystal Structure of α‐F2: Solving a 50 Year Old Puzzle Computationally. Issue 13 (6th February 2019) - Mattsson, Stefan; Paulus, Beate; Redeker, Frenio A.; Beckers, Helmut; Riedel, Sebastian; Müller, Carsten
Abstract: The cohesive energy of α‐fluorine, with C 2/ c space group symmetry, was calculated at benchmark quality by applying the method of increments. The known experimental X‐ray structure data needed to be refined, since the reported intramolecular bond length was unrealistically large. At the CCSD(T) level, including corrections for zero‐point energy, the basis set superposition error, and extrapolated to the complete basis set limit, a cohesive energy of −8.72 kJ mol −1 was calculated, which agrees well with the 0 K‐extrapolated experimental value of −8.35 kJ mol −1 .1 Comparison of the C 2/ c structure with a Cmca structure, isotypic to that of chlorine, bromine, and iodine reveals that the origin of the different structure of solid fluorine, compared to the heavier halogens, is the lack of significantly stabilizing σ‐hole interactions. In addition, the wave numbers of the stretching mode in solid fluorine were calculated at coupled cluster level and compared to newly recorded Raman spectra of condensed fluorine. Both experiment and calculation indicate a slight up‐shift for the stretching mode by 2 or 5 cm −1, respectively, with respect to a free F2 molecule in the gas phase. Abstract : Re‐evaluation : State of the art calculations for α‐F2 rectify the crystal structure determined 50 years ago in X‐ray diffraction experiments. With many‐body expansion methods for electron correlation effects, the experimentally known heat of formation is well reproduced and the calculated vibrational frequencies for α‐F2 agree well with newly recorded Raman spectra.